Early Outcome of Minimally Invasive Direct Coronary Artery Bypass Surgery- A hospital based study (Cardiovascular Journal, 2021)
Background: coronary artery bypass surgery (CABG) is expensive, uses disposable appliances and patients require more perioperative intensive care, long stay in hospital and often have a lengthy recovery time. These complications, together with the growing trend towards less invasive techniques in other areas of surgery, have encouraged cardiac surgeons to see if minimally invasive cardiac surgery can become a reality with improved outcomes and costs.Methods: This is a prospective nonrandomized comparative clinical study done at the Department of Cardiac Surgery in National Institute of Cardiovascular Diseases (NICVD) Sher-E- Bangla Nagar, Dhaka from July 2006 to June 2008 among routine CABG patients. Purposive sampling was done with 26 patients in group A selected for MIDCAB and 24 patients in Group B selected for conventional CABG surgery. Patients were followed up for three months. Postoperative outcomes were assessed to evaluate the safety and efficacy of MIDCAB in relation to conventional CABG.Results: Mean age were 54.19 vs 53.87 in group A and Group B. 92.3% vs 87.5% were male respectively. Mean duration of operation, per operative blood loss transfusion and arrythmia were lower in MIDCAB group (p